Susceptibility of Aedes albopictus skuse (Diptera: Culicidae) to permethrin in Kuala Lumpur, Malaysia - Wan-Norafikah, Othman; Nazni, W.A.; Lee, H.L.; Zainol-Ariffin, P.; Sofian-Azirun, Mohd (2013)
Background: Insects control using insecticides is used extensively and intensively in vector control programs in many countries including Malaysia. Because of this, mosquito species have been found to develop various levels of resistance towards these insecticides, leading to failure in vector control activities. Objectives: We determined permethrin resistance status in laboratory susceptible, permethrin-selected, and field strains of Aedes albopictus. Methods: The susceptibility status of laboratory susceptible strain, permethrin-selected strain, and four field strains of Aedes albopictus collected from Kuala Lumpur were determined using three standard laboratory tests, WHO larval bioassay, WHO adult mosquito bioassay, and microassay of mixed function oxidases (MFOs). Results: The LC50 values of permethrin-selected strain and field strains obtained from the WHO larval bioassay were almost two times higher (0.38-0.44 mg/L) than the LC50 value of the laboratory strain (0.20 mg/L). In the WHO adult bioassay, the susceptibility of permethrin-exposed of both permethrin-selected strain, and field strains (LT50 = 19.39 to 20.65 min) were reduced for 1.31 to 1.72 times after been exposed to the synergist, piperonyl butoxide (PBO) prior to permethrin. Complete mortalities were also recorded in both permethrin-exposed and PBO + permethrin-exposed Ae. albopictus of all strains, twenty-four hours post-exposure. For the MFOs enzyme microassay, a significant difference (p <0.05) in the mean absorbance of elevated oxidase activity at 630 nm was observed between all strains of both the non-exposed and PBO-exposed Ae. albopictus. Strong and significant positive correlations were also observed between LT50 values of permethrin-exposed and PBO + permethrinexposed with oxidase level in Ae. albopictus tested (r = 0.943; p <0.05). Conclusion: These results indicate the association of oxidase activity with permethrin resistance development in Ae. albopictus.